First evidence of globuli ossei in bird (Aves, Spheniciformes): Implications on paleohistology and bird behaviour - García Marsa, Jordi Alexis; Tambussi, Claudia Patricia; Cerda, Ignacio Alejandro (Historical Biology)
Globuli ossei are subspherical structures of endochondral origin that are inserted in the hypertrophic cartilage of long bones, and are related to paedomorphic phenomena. These structures are here described for the first time in Aves, concretely in a postcranial bone of an extinct Spheniciformes from Antarctica (Delphinornis arctowskii). Although it is difficult to infer the significance of the presence of these structures, they appear not to be related to adaptations to aquatic life or depend on the small size or ontogenetic stage of the specimen. A pathological origin for these structures lacks evidence sustaining this hypothesis. The data provided in this contribution reveals that the presence of globuli ossei in vertebrate long bones is not always linked with adaptations to aquatic life and/or paedomorphic processes. Fil: García Marsa, Jordi Alexis. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones en Ciencias de la Tierra; Argentina Fil: Tambussi, Claudia Patricia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones en Ciencias de la Tierra; Argentina Fil: Cerda, Ignacio Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones en Ciencias de la Tierra; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigación en Paleobiología y Geología; Argentina